Financing Vietnam's growth : (Social - Labour Puslishing House, 2009)
Chapter 1: Saving – Investment Balance and Economic Growth in Vietnam / Nguyen Ngoc Son; Chapter 2: Managing Capital Inflows: The case of Vietnam / Vo Tri Thanh and Pham Chi Quang; Chapter 3: The Economic Growth and Foreign Direct Investment in Vietnam: An Empirical Analysis / Nguyen Phi Lan; Chapter 4: On Empirics of Effectiveness of Official Development Assistance (ODA) in Growth in Vietnam / Nguyen Hoang Phuong; Chapter 5: Roadmap for Official Development Assistance (ODA) Mobilization and Utilization in Vietnam / Le Quoc Hoi; Chapter 6: Equitization in Vietnam: Corporate Governance Perspective / Quach Manh Hao; Chapter 7: Development of Corporate Bond Market in Vietnam / Tran Thi Thanh Tu.